2011
DOI: 10.1590/s1677-55382011000600012
|View full text |Cite
|
Sign up to set email alerts
|

Elderly men's quality of life and lower urinary tract symptoms: an intricate relationship

Abstract: Purpose:To evaluate the impact of lower urinary tract symptoms (LUTS) on the quality of life (QoL) in a group of elderly men. Materials and Methods:Observational clinical study contained 200 men recruited between March-September 2008 in the community and Urology and Geriatrics ambulatories. The data collected included health and sociodemographic conditions; the International Prostate Symptom Score (IPSS); an anxiety/depression inventory; the World Health Organization Quality of Life -Bref and -Old questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
(46 reference statements)
1
4
0
1
Order By: Relevance
“…In line with other studies, urinary bladder symptoms constrained HRQoL most ( 25 , 53 , 54 ). High prevalence rates for lower urinary tract symptoms were found in adults over 60 years (men 81%, women 79%), based on a population-based study carried out in five countries ( 7 ).…”
Section: Discussionsupporting
confidence: 91%
“…In line with other studies, urinary bladder symptoms constrained HRQoL most ( 25 , 53 , 54 ). High prevalence rates for lower urinary tract symptoms were found in adults over 60 years (men 81%, women 79%), based on a population-based study carried out in five countries ( 7 ).…”
Section: Discussionsupporting
confidence: 91%
“…The effects of LUTS severity on QoL have been extensively researched [ 27 , 28 , 29 ]. In previous studies, several instruments have been used for the objective evaluation of QoL, showing a decrease in QoL with increasing LUTS severity.…”
Section: Discussionmentioning
confidence: 99%
“…We found lower mean scores in all the domains of the quality of life in the subjects in our study ( P > 0.05; for each domain). Some studies reported that the quality of life is adversely affected by an increase in the severity of LUTS …”
Section: Discussionmentioning
confidence: 99%
“…Benign prostatic hyperplasia, which is the most common urological disease among men in older age, is the main cause of LUTS . A high level of androgen as well as benign prostatic growth leads to an increased risk for LUTS.…”
Section: Introductionmentioning
confidence: 99%